KREATIVITAS RAHAYU SUPANGGAH PADA FILM OPERA JAWA KARYA GARIN NUGROHO - Salim, Muhammad Nur (Acintya, 2020)
ABSTRACT One of the developments in film in Indonesia is the musical genre film. This genre film experienced a post-reform high point when Sherina's Adventure Film came. This point then became the beginning of the development of musical genre films that were born in the 2000s period. One of the interesting musical films is the Javanese Opera Film by Garin Nugroho. Opera Jawa is interesting because first, Opera Jawa has received various awards and nominations at both national and international levels. Second, because this film bases its musical work on Javanese gamelan or gamelan media. This second reason is the focus of this research. The research "Rahayu Suanggah's Creativity in Garin Nugroho's Javanese Opera Film" is an attempt to reveal one of the film music creation methodologies based on her creative process with Javanese karawitan media (gamelan music). The musical concepts of the musical that were carried by Rahayu Supanggah as the music director was revealed through Rahayu Supanggah's conceptual approach in Bothekan Karawitan Garap's book (2007). The results of this study; Rahayu Supanggah uses Javanese musical nuances in composing Javanese Opera music by involving songs that are composed in various variations such as; 1) single tembang, 2) pathetan, 3) nothing, 4) palaran, and 5) arrangement of traditional pieces while the illustration music consists of 1) New Composition, 2) Illustration of Traditional Music, 3) Exploration Music. Keywords: Creativity, Music, Javanese Opera, Rahayu Supanggah  ABSTRAK Perkembangan film di Indonesia salah satunya pernah diwarnai oleh film genre musikal. Film genre ini mengalami titik puncak pasca reformasi ketika Film Petualangan Sherina hadir. Titik tersebut kemudian menjadi awal perkembangan film genre musikal yang lahir pada periode tahun 2000-an. Salah satu film musikal yang menarik adalah Film Opera Jawa karya Garin Nugroho. Opera Jawa menarik karena pertama, Opera Jawa mendapatkan berbagai penghargaan dan nominasi tingkat nasional maupun internasional. Kedua, karena film ini mendasarkan garapan musikalnya dengan media gamelan Jawa atau karawitan. Alasan kedua inilah yang menjadi fokus pada penelitian ini.Penelitian “Kreativitas Rahayu Suanggah dalam Film Opera Jawa Karya Garin Nugroho” merupakan upaya mengungkap salah satu metodologi penciptaan musik film yang mendasarkan proses kreatifnya dengan media karawitan Jawa (musik gamelan). Konsep-konsep musikal karawitan yang diusung Rahayu Supanggah sebagai music director diungkap melalui pendekatan konsep garap-nya Rahayu Supanggah dalam buku Bothekan Karawitan Garap (2007). Hasil penelitian ini; Rahayu Supanggah menggunakan nuansa karawitan Jawa dalam menggarap musik Opera Jawa dengan melibatkan tembang yang digarap dalam berbagai variasi seperti; 1) tembang tunggal, 2) pathetan, 3) ada-ada, 4) palaran dan 5) aransemen gendhing tradisi sedangkan musik ilustrasi terdiri dari 1) Komposisi Baru, 2) Ilustrasi Gending Tradisi, 3) Musik Eksplorasi.Kata Kunci: Kreativitas, Musik, Opera Jawa, Rahayu Supanggah